2019
DOI: 10.3390/min9120785
|View full text |Cite
|
Sign up to set email alerts
|

Dewatering of Mine Tailings Slurries Using Superabsorbent Polymers (SAPs) Reclaimed from Industrial Reject of Baby Diapers: A Preliminary Study

Abstract: Traditional deposition of tailings slurry in a tailings storage facility (TSF) can create risks of dike failure. In order to minimize these risks and slurry spillage, the surface deposition technique of densified tailings (DT) through dewatering of the slurry has emerged. The DT technique has the potential to maximize water reuse, improve the shear strength of surface tailings, and reduce the ecological footprint of TSF. The consistency of DT covers a continuum ranging from thickened state, to paste state, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Large-scale application of SAPs is limited because of high costs and difficulties in scaling up the technology. Preliminary work by Sahi et al (2019) demonstrated that SAPs can be reclaimed and reused, 80 but desorbing the water incurs additional operating and equipment costs.…”
Section: Design and Construction Of Stackedmentioning
confidence: 99%
“…Large-scale application of SAPs is limited because of high costs and difficulties in scaling up the technology. Preliminary work by Sahi et al (2019) demonstrated that SAPs can be reclaimed and reused, 80 but desorbing the water incurs additional operating and equipment costs.…”
Section: Design and Construction Of Stackedmentioning
confidence: 99%
“…However, this cost comparison ignores cost reductions due to increased process water recovery, the reduced storage volume required with increasing tailings dewatering, the consequently reduced containment required, and With increasing the mechanical dewatering of tailings, costs increase dramatically. Thickening is about 1.5 times more costly than conventional slurry tailings, high-density thickening about 3 times more costly, paste about 8 times more costly, and filtration about 27 times more costly than slurry tailings [31]. However, this cost comparison ignores cost reductions due to increased process water recovery, the reduced storage volume required with increasing tailings dewatering, the consequently reduced containment required, and the reduced cost of rehabilitation and enhanced potential post-closure land use.…”
Section: Filtration and Dry Stackingmentioning
confidence: 99%
“…An alternative involves the application of a polyacrylic acid such as sodium polyacrylate (NaPA), which is a low molecular weight polymer with properties and a chain length that can be modified through varying reaction conditions [2]. This polymer has an interesting behavior that can be used in many applications [3][4][5][6][7], including in the lithium industry [8] and tailing treatment in mining operations [9,10]. In the context of mineral processing, it finds common usage in the mining industry as a dispersant additive for enhancing the flotation stage's efficiency and improving tailings fluidity.…”
Section: Introductionmentioning
confidence: 99%